Upaya Peningkatan Kompetensi Bahasa Inggris Mahasiswa Jurusan Tarbiyah Program Studi Pendidikan Agama Islam (PAI) STAIN Curup Dan Relevansinya Terhadap TOEFL Score Sebagai Syarat Wisuda - Noviyenty, Leffi (BELAJEA: Jurnal Pendidikan Islam, 2018)
This is a descriptive qualitative research which investigates English Competence of PAI students in STAIN Curup, studentsâ problems in facing TOEFL as one of graduation requiremnets in STAIN Curup. All PAI students who followed TOEFL is taken as sample of this research. Document analysis and deep interview are the techniques of collecting data. The informan are selected from Unit Pengembangan Bahasa (UPB)âs tutors and staff who responsible to held TOEFL. Data analysis is developed by comparing the three basic components, data reduction, data presentation and data conclusion/verification. The findings show that 1. PAI studentsâ English competence on TOEFL needs to be improved since their average score is 351 and only 4 students got above 400 score ; 2. The problems they face on TOEFL are the material of TOEFL is not yet familiar to them, the studentsâ attitude toward TOEFL is still low, English subjects during college are not enough to develop their English ability, even the lesson in English subjects is not relevan with TOEFL material, and there is no solution from the institution to help the students preparing TOEFL, so they can only solve the problem themselves; 3. Most of English lecturers are agree to develop a particular learning model for PAI students in preparing TOEFL.